Special Issue on New Industry 4.0 Advances in Industrial IoT and Visual Computing for Manufacturing Processes - de Lacalle, Luis Norberto López; Posada, Jorge (Applied sciences, 2019)
The new advances of IIOT (Industrial Internet of Things), together with the progress in visual computing technologies, are being addressed by the research community with interesting approaches and results in the Industry 4 [...]